2018
DOI: 10.1007/s12035-018-1032-x
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Expression Levels Are Altered in the Cerebrospinal Fluid of Patients with Young-Onset Alzheimer’s Disease

Abstract: Clinical diagnosis of Alzheimer’s disease (AD) prior to the age of 65 years is classified as young-onset (YOAD), whereas diagnosis after the age of 65 years is considered late-onset (LOAD). Although rare autosomal mutations more commonly associate with YOAD, most YOAD and LOAD cases are sporadic. YOAD and LOAD share amyloid and tau pathology, but many YOAD patients show increased disease severity and rate of progression. The current study examined the microRNA (miRNA) expression profile from exosomes isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
117
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(130 citation statements)
references
References 121 publications
3
117
1
1
Order By: Relevance
“…Moreover, recent researches have shown that the dysregulation of microRNAs (miRNAs) may link to Aβ accumulation in AD patients as well as in MCI patients . It is also demonstrated that the abnormity of miRNAs such as miR‐144‐3p and let‐7g‐5p could be found in both MCI and AD patients, but very few evidence could verify the correlation between miRNAs and oxysterols in MCI patients.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recent researches have shown that the dysregulation of microRNAs (miRNAs) may link to Aβ accumulation in AD patients as well as in MCI patients . It is also demonstrated that the abnormity of miRNAs such as miR‐144‐3p and let‐7g‐5p could be found in both MCI and AD patients, but very few evidence could verify the correlation between miRNAs and oxysterols in MCI patients.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have also strived to distinguish between youngand late-onset AD (YOAD/LOAD). McKeever et al (2018) collected CSF samples from 17 YOAD patients, 13 LOAD patients, and 12 healthy controls; they found that CSF-derived ex-miR-125b-5p was increased in YOAD patients, whereas ex-miR-16-5p, ex-miR-451a, and ex-miR-605-5p were decreased. In addition, the altered levels of ex-miR-125b-5p, ex-miR-451a, and ex-miR-605-5p were similar in both LOAD and YOAD patients when compared with the healthy controls.…”
Section: Ex-mirnas As Biomarkers In Admentioning
confidence: 99%
“…It has been reported that alterations in CSF miRNAs can reflect the changes of miRNAs in brain pathological tissue better than those in blood or postmortem brain samples. 40 There are two reasons for this phenomenon: 41,42 (1) In view of the inherent limitations associated with obtaining brain tissue in vivo, most human studies use postmortem samples to study miRNA expression. However, the study of postmortem brain tissue may be confounded by an extended postmortem interval and prior medication exposure; (2) Peripheral blood may not closely reflect gene expression levels in the brain.…”
Section: Mirnas In Cerebrospinal Fluid (Csf) Examinationmentioning
confidence: 99%